Experimental and analytical investigations on corroded reinforced concrete slab - Yang, Zhihong (Nanyang Technological University, 2023)
Reinforced concrete (RC) flat slabs are indispensable members within RC structures because they maintain structural integrity. Under monotonic or seismic loadings, the flat slab represents the most vulnerable region. If it were to fail during punching shear, the structural system would be affected, and it would lead to the rapid collapse of the structure. More seriously, corrosion of reinforcements causes the load capacity and durability of RC slab to deteriorate and increases the probability of shear failure. There has therefore been a pressing concern to assess the security of existing corroded RC flat slabs and to decide the appropriate time to repair or to strengthen them according to their residual capacity at that particular time. In this research, experimental studies on RC slabs under punching shear loading were conducted. A total of 8 corroded and un-corroded specimens were tested to investigate their strengths and failure modes. Punching shear strength, stiffness, crack pattern, energy dissipation and failure mode, amongst other factors, were examined. The punching shear strength of the corroded RC slabs was drastically reduced, according to experimental data. Additionally, it was shown that specimen failure modes changed with increasing corrosion, moving from punching shear failure to flexural failure. Numerical work was done to better estimate and investigates the punching shear mechanisms in the corroded RC slabs. A calibrated and validated 3-dimensional (3D) non-linear FE model was proposed considering the material deterioration and bond degradation. This can be utilized to estimate the ultimate shear strength of corroded RC slabs with various corrosion levels, reinforcement ratios, compressive concrete strengths, and slab thicknesses efficiently. A thorough parametric analysis was conducted to look into any additional factors that might have an impact on punching shear strength. Empirical equations for forecasting the punching shear strength of corroded RC slabs were suggested and validated based on the analytical studies of the parametric study. Additionally, using the newly developed Critical Shear Crack Theory, the behaviour of corroded RC slabs was examined (CSCT). A deteriorated bond mechanism and material properties owing to the corrosion of reinforcements were incorporated into the CSCT model. The potential suggested model showed good agreement with and the experimentally determined punching shear strength as well as failure mode. A parametric study was also proposed on the basis of the CSCT so as to study its impact on the failure mode and residual strength of the corroded RC slabs. The results indicated that an increase in corrosion level, decrease in reinforcement ratio and reduction in slab thickness would result in the failure mode of the corroded RC slabs being converted from fail in punching shear to fail in flexure. Apart from the study of corroded slab under monotonic loading, further investigation on the seismic behaviour of corroded slab-column joints was conducted. A FE model of slab-column joint was utilized by considering the effect of corrosion on mechanical properties of rebar as well as concrete deterioration. Owing to the limitations of the experimental data, the numerical results were verified by several un-corroded slab-column joints subjected to cyclic loading in the literature. A parametric study was conducted so as to observe the effect of some crucial factors that might affect seismic behaviour of the corroded RC slab. After that, empirical formulas were proposed to estimate the ultimate moment capacity of interior and exterior corroded slabs on the basis of the multivariable regression analysis of the parametric study.